Soyica Ariari-1, variedad mejorada de soya (Glicine max (L) Merril)para suelos de vega del Piedemonte Llanero (1990)
Soyica Ariari-1 is a improved soybean variety created by the Program of Legume and Oil Grain of the Instituto Colombiano Agropecuario ICA. It was obtained from a cross VI x (Jupiter x F66-1 534), made by Florida de University (USA) for tropical conditions. The variety is appropiate for alluvial soils of the "Llanos Orientales" with elevation between 300 and 1000 masl and a temperature between 24 and 30°C. It has a determinate growth, a plant height ranging from about 19 to 26 inch and a vegetative period ranging from about 100 to 105 days. It is characterized by purple flo- wers, dark green leaves, and reddish brown pubescens. It shows tolerance to the frogeye leaf spot (Cercospora sojina). Grain yield ranges from 1.9 to 3.4 t/ha. In commercial trials the grain yield was 19% more than the control. The grain yields were similar in several semester, the new variety show better stability of perfomed in adverse conditions. The new variety produced a net income of $124.412 per hectar, which means 61.2% revenue when was compared to the control SV-89 (39.5%).